Menstrual disturbances in British Servicewomen: A cross-sectional observational study of prevalence and risk factors - O'Leary, Thomas J.; Perrett, Caitlin; Coombs, Charlotte V.; Double, Rebecca L.; Keay, Nicky; Wardle, Sophie L.; Greeves, Julie P. (Frontiers in Nutrition, 2022)
Female athletes are at increased risk of menstrual disturbances. The prevalence of menstrual disturbances in British Servicewomen and the associated risk factors is unknown. All women under 45 years in the UK Armed Forces were invited to complete a survey about demographics, menstrual function, eating and exercise behaviours, and psychological wellbeing. 3,022 women participated; 18% had oligomenorrhoea or amenorrhoea in the last 12 months, 25% had a history of amenorrhoea, and 14% had delayed menarche. Women who sleep ≥ 8 hours were at a lower risk of a history of amenorrhoea than women who sleep ≤ 5 hours (odds ratio [95% confidence intervals] = 0.65 [0.48, 0.89], p = 0.006). Women who completed > 10 days of field exercise in the last 12 months were at higher risk of a history of amenorrhoea than women completing no field exercise (1.45 [1.13, 1.85], p = 0.004). Women at high risk of an eating disorder (FAST score >94) were at higher risk of oligomenorrhoea or amenorrhoea (1.97 [1.26, 3.04], p = 0.002) and history of amenorrhoea (2.14 [1.63, 2.79], p < 0.001). Women with anxiety or depression were at higher risk of a history of amenorrhoea (1.46 [1.20, 1.77] and 1.48 [1.22, 1.79], p < 0.001). British Servicewomen had a similar prevalence of menstrual disturbances to some endurance athletes. Eating disorders, sleep behaviours, and management of mental health, provide targets for protecting health of the reproductive axis.